Studi Drill Rate Indeks (DRI) Pada Kegiatan Pengeboran Lubang Tembak Pada Formasi Balikapan dan Formasi Pulaubalang PT. Bukit Baiduri Energi Dan PT. Khutai Makmur Insan Abadi Provinsi Kalimantan Timur - Ibnu Syafi’i Rhamadany; Tommy Trides; Windhu Nugroho (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Rotary drilling is one of the drilling methods that is often used for stripping overburden in open pit mining activities. In the rotary drilling process, prediction of the penetration rate is very important for scheduling production and estimating drilling costs. Drilling in mining activities is used, among other things, to create blast holes. In blasting activities, drilling is the first activity that must be carried out to provide a blast hole which will later be filled with explosives to be detonated. Meanwhile, the speed at which the blast hole is prepared is influenced by the speed of the drilling tool to penetrate the rock. Drilling speed is influenced by two factors, namely internal factors and external factors.